HealthGrid applications and technologies meet science gateways for life sciences - HealthGrid 2012 (2012 : Amsterdam, Netherlands); Gesing, Sandra; IOS Press; IWSG-Life 2012 (2012 : Amsterdam, Netherlands) (Amsterdam ; Washington, D.C. : IOS Press, 2012)
The integration of grid, cloud and other e-infrastructures into the fields of biology, bioinformatics, biomedicine, and healthcare are crucial if optimum use is to be made of the latest high-performance and distributed computer technology in these areas. Science gateways are concerned with offering intuitive graphical user interfaces to applications, data, and tools on distributed computing infrastructures. This book presents the joint proceedings of the Tenth HealthGrid Conference and the Fourth International Workshop on Science Gateways for Life Sciences (IWSG-Life), held in Amsterdam, Netherlands in May 2012. The HealthGrid conference promotes the exchange and debate of ideas, technologies and solutions likely to promote the integration of grids into biomedical research and health in the broadest sense. The IWSG-Life workshop series is a forum that brings together scientists from the field of life sciences, bioinformatics, and computer science to advance computational biology and chemistry in the context of science gateways. These events have been jointly organized to maximize the benefit from synergies and stimulate the forging of further links in joint research areas. The book is divided into three parts. Part I includes contributions accepted to the HealthGrid conference; Part II contains the papers about various aspects of the development and usage of science gateways for life sciences. The joint session is recorded in Part III, and addresses the topic of science gateways for biomedical research. The book will provide insights and new perspectives for all those involved in the research and use of infrastructures and technology for healthcare and life sciences.
Title Page; Preface; Committees; Contents; Part I. HealthGrid Applications and Technologies; HealthGrid 2012; Section 1. HealthGrid Scientific Papers; Federated Queries for Comparative Effectiveness Research: Performance Analysis; A System Architecture for Sharing De-Identified, Research-Ready Brain Scans and Health Information Across Clinical Imaging Centers; A Flexible, Open, Decentralized System for Digital Pathology Networks; eLab: Bringing Together People, Data and Methods to Enhance Knowledge Discovery in Healthcare Settings.
Includes indexes.
Includes bibliographical references and indexes.
English.
eBooks on EBSCOhost
Keywords: Medical informatics -- Congresses; Biomedical Research; Médecine -- Informatique -- Congrès.; MEDICAL -- Allied Health Services -- Medical Technology; MEDICAL -- Biotechnology; MEDICAL -- Family & General Practice; MEDICAL -- Lasers in Medicine; TECHNOLOGY & ENGINEERING -- Biomedical; Medical informatics; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.